2019
DOI: 10.1186/s42269-019-0180-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in a group of Egyptian children and adolescents with type 1 diabetes: relationship to microvascular complications

Abstract: Background: The increased prevalence of type 1 diabetes mellitus in children and adolescents with its complications, especially microvascular ones (retinopathy, nephropathy, and neuropathy) that affect the expectancy of their lives, besides imposing restrictions on their physical, emotional, and social functioning, adversely affecting their quality of life, in turn would lead to worsening of their compliance and adherence to the treatment with subsequent hazards on metabolic control, development, and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
1
2
0
Order By: Relevance
“…Majority of the mean level of HbA1C from our study was more than 7%. In line with other studies conducted in Turkey, Egyptian as well as research in Khartoum also reported similar finding that was reflected that the most of the children that involved in the studies had poor glycemic control [18], [19], [20]. Low parental education levels, low economic income, and limitation of the health care service were postulated as the cause of poor glycemic control in children with T1DM [20].…”
Section: Discussionsupporting
confidence: 86%
“…Majority of the mean level of HbA1C from our study was more than 7%. In line with other studies conducted in Turkey, Egyptian as well as research in Khartoum also reported similar finding that was reflected that the most of the children that involved in the studies had poor glycemic control [18], [19], [20]. Low parental education levels, low economic income, and limitation of the health care service were postulated as the cause of poor glycemic control in children with T1DM [20].…”
Section: Discussionsupporting
confidence: 86%
“…Individuals experiencing complications may fear judgment from their healthcare team and may experience shame and self-criticism, which may contribute to overall coping as well as delays in seeking treatment and routine screenings [114]. Studies have found that the experience of neuropathy contributes to greater levels of distress, depression, and diminished quality of life [115,116]. In a piece in the journal PLAID: People Living with And Inspired by Diabetes, writers Chris Aldred and Renza Scibilia advocate for increased open, nonjudgmental communication about complications and state: "If people felt comfortable sharing stories about complications, it would reduce feelings of isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found no difference between children with T1D and their healthy peers [ 4 ]. Studies suggest that male gender, longer diabetes duration, better glycemic control and higher socioeconomic status are associated with better HRQoL [ 5 7 ]. Less favorable HRQoL was associated with youths' perceptions that diabetes is upsetting, difficult to manage, and stressful, as well as fear of hypoglycemia [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%